Effect of the Use of Noni Leaf Extract as a Natural Disinfectant on the Percentage of Hatchability and Day Old Quail (DOQ) Hatching - Muhammad Nur Hidayat; Amina Hajah Thaha; Reny Mayanti (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2019)
This study aims to determine the effect of noni leaf (Morinda citrifolia lignosae) extract as a natural disinfectant on the percentage of hatchability and the hatchability weight of quail (Coturnix-coturnix japonica). This study used 1,500 quail hatch eggs with a male and female parent ratio of 1: 4. This study used a Completely Randomized Design (CRD) method, with five treatments and three replications each repetition consisting of 100 quail eggs with 10-gram weight. The treatments used were: T0 (control treatment), T1 (commercial disinfectant), T2 (noni leaf extract 10%), T3 (noni leaf extract 20%) and T4 (noni leaf extract 30%). The results of variance showed the average percentage of hatchability produced during the study, namely T0 (85%), T1 (83%), T2 (86%), T3 (84%), and T4 (93%). Furthermore, the average weight of hatchability produced, namely T0 (6.67 grams), T1 (6.76 grams, T2 (6.89 grams), T3 (6.84 grams) and T4 (6.89 grams). Overall administration of noni leaf extract had no significant effect (P 0.05) on the percentage of hatchability and DOQ hatching weight of the quail.